O processo de projeto contemporâneo: análise sobre estratégias projetuais - Sibelle Meyer Lana (2023)
Creativity has been a topic of discussion, both in architecture education and in professional practice. Literature considers creativity a skill that can be developed, but not taught. In this context, different paths have been observed in relation to the procedures used by contemporary professionals, which are often contradictory, accompanied by worries. Traditionally, the architecture and urbanism project is considered a resolutive action, a response to a problem or demand presented, which results in some design alternatives. The project transcends representation, design and technique. It expresses the development of a thought, which means, it is configured in a project process. Due to the absence of a single alternative, the differential between the possible solutions in this process is investigated in this thesis. The research aims at understanding the relationship between the design strategies used, and the construction of tectonics. We work with the hypothesis that the dialogue between technique and creativity occurs through the domain of the construction system. It is believed that the experience of space and constructive authority expand vocabulary, repertoire and, consequently, enhance creative capacity within the process. In order to map the recurrent procedural elements in the construction of tectonics, the analysis of the design and its processes, adopted by some contemporary professionals, is proposed as a methodology. The study highlights the graphic, textual and verbal elements, in addition to some details intrinsic to the architecture. The processes used by the selected professionals and the works are studied, through the identification of the correlation between the analysis made of the project premises - urban insertion, program and construction system - and the tectonics, as a form of generating knowledge.